Studying the effect of particulate matter as SARS-CoV-2 transmitters - Abdulrahim R. Hakami; Gasim Dobie (Journal of Public Health Research, 2021)
Background: Studies of risk factors are especially valuable at this difficult time in the midst of a pandemic. High levels of particulate matter (PM) represent a serious risk factor on health. While this is a direct impact on health, indirect effects are worth considering too. Design and Methods: The aim of this study was to investigate the role of PM in the transmission of viruses, especially SARS-CoV-2. Also, we sought to understand dynamics of PM in still air at high and low altitudes. Historic AQI and physical PM measurements were collected between August and September 2020 using air quality detector. Potential correlations between the number of total confirmed COVID-19 cases and average air quality index (AQI) from varied geographic locations were also assessed. Results: Airborne PM levels were weakly associated with COVID-19 cases after analysing 77 territories. PM remained longer in the air at high altitudes compared to measurements made at sea level. This suggests that the link between PM and COVID-19 transmission could be aggravated in areas of high altitude. Conclusions: This article highlights that particulate matter can be involved in SARS-CoV-2 transmission. However, confounding factors may have impacted the association between the two variables. These findings can serve as a foundation for future studies on the effect of air pollutants and fine particulate matter on viral transmission.